2020
DOI: 10.1088/1475-7516/2020/11/045
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy-lens determination of H0: constraining density slope in the context of the mass sheet degeneracy

Abstract: Gravitational lensing offers a competitive method to measure H0 with the goal of 1% precision. A major obstacle comes in the form of lensing degeneracies, such as the mass sheet degeneracy (MSD), which make it possible for a family of density profiles to reproduce the same lensing observables but return different values of H0. The modeling process artificially selects one choice from this family, potentially biasing H0. The effect is more pronounced when the profile of a given lens is not perfectly described b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Reanalyzing data by relaxing strong assumptions is a useful way to check those assumptions. This philosophy has been used to check the validity of other astrophysical assumptions as well, such as in the strong-lensing time-delay technique of determining the Hubble constant [62,91,92]. In the future, galaxy surveys such as the Dark Energy Spectroscopic Instrument (DESI) will provide measurement of BAO with unprecedented precision [93].…”
Section: I)mentioning
confidence: 99%
“…Reanalyzing data by relaxing strong assumptions is a useful way to check those assumptions. This philosophy has been used to check the validity of other astrophysical assumptions as well, such as in the strong-lensing time-delay technique of determining the Hubble constant [62,91,92]. In the future, galaxy surveys such as the Dark Energy Spectroscopic Instrument (DESI) will provide measurement of BAO with unprecedented precision [93].…”
Section: I)mentioning
confidence: 99%
“…Methods of breaking MSD have been intensively investigated and could be classified as two catagories, i.e. assuming theoretical priors (Navarro et al 1997;Millon et al 2020;Gomer & Williams 2020;Denzel et al 2021) and appealing non-lensing stellar kinematics data (Birrer et al 2020;). More recently, Ding et al (2021) carried out realistic simulations in lens modeling based on HST WFC3 observations from transient sources (e.g.…”
Section: Uncertainty Estimationmentioning
confidence: 99%
“…Hsueh et al (2017) showed that the flux ratio anomalies observed in lens system CLASS B0712+472 can be largely resolved by additionally adding a disk profile to the lensing model. The works of Gomer & Williams (2020; Cao et al (2021); Van de Vyvere et al (2021) show that such mismatches can impact on the inference of the Hubble constant via time-delay cosmology.…”
Section: Other Lensing Studiesmentioning
confidence: 99%